2018
DOI: 10.1155/2018/1659089
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Antenatal Depression and Associated Factors among Pregnant Women Attending Antenatal Care at Dubti Hospital: A Case of Pastoralist Region in Northeast Ethiopia

Abstract: Background. Globally, depression affects an estimated 10 % to 20% of women during pregnancy. There is limited evidence on antenatal depression in Northeast Ethiopia. This study aimed to assess prevalence of antenatal depression and associated factors among Dubti Hospital Antenatal care attendants. Methods. Institution based cross-sectional study was conducted among 363 Antenatal care attendants at Dubti Hospital from March 07 to May 07, 2016. Beck’s Depression Inventory tool was used to collect data. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 37 publications
10
33
2
1
Order By: Relevance
“…Bivariable logistic regression analysis showed that maternal education, average family monthly income, history of complication in previous pregnancy, and previous history of depression were statistically associated with antenatal depression in Northern Ethiopia Dubti Hospital (37).…”
Section: Determinants Of Antenatal Depressionmentioning
confidence: 96%
See 3 more Smart Citations
“…Bivariable logistic regression analysis showed that maternal education, average family monthly income, history of complication in previous pregnancy, and previous history of depression were statistically associated with antenatal depression in Northern Ethiopia Dubti Hospital (37).…”
Section: Determinants Of Antenatal Depressionmentioning
confidence: 96%
“…The prevalence of antenatal depression is reported to be 31.2% in Adama Hospital among 345 pregnant mothers attending ANC at public health center by using BDI II (31), 31.1 % in Maichew among 209 women attending antenatal care of the total women attending ANC follow up out of the source population of 600 pregnant mothers in public health centers using beck depression inventory to assess individual's depression condition with a cutoff point greater or equals to 14 (32), 29.5% in Sodo district of Gurage Zone among 254 pregnant mothers with BDI I with a cutoff point greater or equals to 14 (33) . 24.9%inAddis Ababa Public Health Centers among 542 pregnant mothers attending ANC follow up at public health center by using BDI I with a cutoff point greater or equals to 14 (34).23% in Gondar University Hospital among 388 pregnant mothers attending ANC follow up at Gonder University Hospital with BDI (35,36) and a recent study in Dubti hospital located 10 Km from Samara which is the capital city of Afar Regional state with prevalence of 17.9% and the sample size was 363 among a total of 4560 women following antenatal care per one year and the research was conducted with Beck depression inventory II with a cutoff point > or equals to 17 to assess the individual's depression condition (37).…”
Section: Prevalence Of Antenatal Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…La depresión está actualmente considerada un problema de salud pública con gran prevalencia mundial (Davis, Goodman, Leiferman, Taylor, & Dimidjian, 2015), siendo catalogada por la Organización Mundial de la Salud (OMS) como el mayor contribuyente a la discapacidad global en 2015 (WHO, 2017). Asimismo, según Belay, Moges, Hiksa, Arado, & Liben (2018), la depresión prenatal queda definida como la aparición de un proceso depresivo durante el embarazo y que afecta al 10-20 % de las mujeres gestantes a nivel mundial. Las mujeres con depresión prenatal presentan un aumento del riesgo de padecer depresión posparto, insatisfacción conyugal, escaso apoyo social, posteriores problemas de estrés parental (Goodman & Tully, 2009;Misri et al, 2010), prematuridad del parto (Field et al, 2009), retrasos del desarrollo (Deave, Heronm, Evans, & Edmond, 2008) y, además, según de Bruijn, van Bakel, y van Baar (2009), sus futuros hijos tendrán mayor posibilidad de sufrir problemas de conducta tanto en su infancia, como en su etapa adolescente (Hay, Pawlby, Waters, Perra, & Sharp, 2010).…”
Section: Introductionunclassified